Community Concern in Responding to Religious Education for Youth People in Aceh Singkil - Salminawati; Yusnaili Budianti; Salama (Graduate Program Magister Manajemen Pendidikan, 2023)
This study aims to identify the condition of youth religious education in the village of Lipat Kajang Atas, Kec. Simpang Kanan Kab. Aceh Singkil. To identify community concerns regarding youth religious education in Lipat Kajang Atas Village, Simpang Kanan District, Aceh Singkil District. The approach used in this research is a qualitative naturalistic approach, namely collecting and analyzing data that is qualitative in nature and the research is carried out in natural conditions (natural setting). This research is related to social interaction regarding community concern for adolescent religious education. The result of this research is to provide religious guidance to teenagers in the vicinity through religious activities such as routine recitation, participating in dhikr khairat activities, and persulukan. As for other things, the results of this study provide guidance and role models for children and adolescents always to maintain a polite attitude and introduce positive culture to them.